Hypoxia and TGF-β1 lead to endostatin resistance by cooperatively increasing cancer stem cells in A549 transplantation tumors. Issue 1 (December 2015) - Wang, Yuyi; Jiang, Ming; Li, Zhixi; Wang, Jiantao; Du, Chi; Yanyang, Liu; Yu, Yang; Wang, Xia; Zhang, Nan; Zhao, Maoyuan; Wang, Li; Li, Mei; et al.
Abstract Background Lung cancer is the leading cause of cancer-related deaths worldwide, and treatments for lung cancer have a high failure rate. Anti-angiogenic therapy is also often ineffective because of refractory disease. Endostatin (ES) is one of the most widely-used anti-angiogenic drugs for lung cancer in China, and resistance to it is a barrier that needs to be resolved. It has been shown that myeloid-derived suppressor cells (MDSCs) are involved in resistance to ES. Whether other cells and/or cell factors in the tumor microenvironment that have been shown to be related to resistance to other anti-cancer drugs are also involved in ES resistance is unknown. Results In this study, we showed that after continuously treatment with ES for 12 days, volumes of A549 transplantation tumors of mice reached the sizes of tumors which were borne by mice that were treated with normal saline and this meant that resistance to ES appeared. Cancer stem cells (CSCs), which have been widely accepted as one of reasons responsible for resistance to many anti-tumor drugs were also being discovered increased proportionally in A549 transplantation tumors after ES treatment for 12 days. During further exploration of reasons for this increase, we discovered that after ES treatment, microvessel density and vascular endothelial growth factor level was decreased in tumors, whereas transforming growth factor (TGF)-β1 level was elevated, and MDSCs, one of the sources of TGF-β1, were also increased. We speculate that hypoxia and TGF-β1 are responsible for the increased CSC number in A549 transplantation tumors. By using cobalt chloride to mimic hypoxia and human recombinant TGF-β1 in vitro, we found that hypoxia and TGF-β1can indeed enhance the stemness of A549 cells. In addition, the inductive effect of hypoxia is stronger than TGF-β1, and the combination of both is stronger than either alone, which is first report of such a finding, to our knowledge. Conclusions Increased TGF-β1 and strengthened hypoxia in A549 transplantation tumors, as a result of ES therapy, cooperatively increase proportion of CSCs that are involved in ES resistance which was revealed by failure of tumor volume repression after continuously treatment with ES for 12 days.